THE INFLUENCE OF PLACEMENT AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT THE POPULATION AND CIVIL REGISTRY SERVICE OF PANGKEP REGENCY - Ghelvira Nurfatimah; Sri Andayaningsih; Zalkha Soraya (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
Employee performance is a critical determinant of public service quality, particularly within government institutions. This study examines (a) the effect of job placement on employee performance and (b) the effect of work experience on employee performance at the Population and Civil Registration Office of Pangkep Regency. Using a quantitative approach, data were collected from 47 civil servants selected through saturated sampling. Questionnaires served as the primary data collection tool, and the data were analyzed with SPSS 25 using descriptive statistics, instrument testing, classical assumption tests, multiple linear regression, and hypothesis testing. The results show that job placement does not have a significant positive impact on employee performance, suggesting that proper placement alone is insufficient to enhance outcomes. Conversely, work experience exerts a significant positive influence, indicating that accumulated knowledge and practical expertise contribute to improved employee performance in service delivery. These findings highlight the importance of organizational strategies that strengthen employee experience through training and continuous professional development to enhance public sector service quality.